Equity of access to palliative care: a scoping review - Gonçalo Sítima; Carlos Galhardo-Branco; Paulo Reis-Pina (BMC, 2024)
Abstract Background Palliative care (PC) has the potential to alleviate suffering and enhance quality of life for patients with serious progressive diseases; however, access to PC remains unequal across different populations. Objective This scoping review aimed to systematically examine the literature on: (1) the primary contributors to inequity in accessing PC; (2) the key barriers to achieving equitable access to PC; (3) the essential recommendations for addressing these issues. Methods The PubMed, Web of Science, and Embase databases were searched for English-language articles published since 2017. Eligibility criteria: Population- people with chronic, progressive, life-threatening, or limiting diseases. Interventions- any PC intervention, including teams, services, programs, or strategies implemented in both hospital and community settings. Outcomes- equity in access to PC. Study Design- any. The PRISMA (extension for scoping reviews) recommendations were followed. Results Fourteen studies were included: half originated from North America (USA, n = 5; Canada, n = 2) and the other half from Europe (UK, n = 4; Spain, n = 1) and Australia (n = 2). Most studies focused on ethnic/racial discrimination (n = 4) or geographical discrepancies (n = 4). The remaining studies addressed PC in low- or middle-income countries (n = 2), gender discrepancies (n = 1), informal caregiving (n = 1), socioeconomic inequities (n = 2), and barriers to accessing PC (n = 1). Barriers to equitable access to PC include difficulties in identifying patients nearing the end of life, the "survival imperative," the "normalization of dying," misconceptions, mistrust, limited information about PC and end-of-life care, and a fragmented care system. Conversely, enablers of equitable access to PC encompass proper patient evaluation and workforce education, addressing basic survival needs and social determinants of equity, and promoting intersectoral collaboration, community advocacy, and engagement. Conclusion Achieving equity in PC is a complex endeavor requiring strong commitment and action at both policy and governmental levels. Additionally, it calls for sustained efforts in clinical practice, workforce planning, capacity building, community engagement, and research investment to implement and assess public health approaches to PC. Future research should aim to provide more comprehensive and generalizable insights into the determinants of equitable access, as well as the enablers and barriers to PC and end-of-life care.